2009
DOI: 10.3174/ajnr.a1497
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Nerve Root Changes on Contrast-Enhanced MR Imaging after Surgery for Lumbar Disk Herniation

Abstract: BACKGROUND AND PURPOSE:The significance of postoperative nerve root changes (enhancement, thickening, and displacement) is still a topic of debate. The purpose of this study was to evaluate the association between nerve root changes and residual or recurrent symptoms after lumbar surgery with contrast-enhanced MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…This correlation was stronger in the presence of both nerve root thickening and recurrent disc herniation [129]. When NRE was combined with nerve root thickening, the PPV increased to 87.7%, and when recurrent disc herniation was also identified, the PPV increased to 94.1% [129]. Other information that can be revealed by MRI includes stenosis in the lateral recess and neural foramens, diskitis, and pseudomeningocele [68,128].…”
Section: Patient Evaluationmentioning
confidence: 98%
See 2 more Smart Citations
“…This correlation was stronger in the presence of both nerve root thickening and recurrent disc herniation [129]. When NRE was combined with nerve root thickening, the PPV increased to 87.7%, and when recurrent disc herniation was also identified, the PPV increased to 94.1% [129]. Other information that can be revealed by MRI includes stenosis in the lateral recess and neural foramens, diskitis, and pseudomeningocele [68,128].…”
Section: Patient Evaluationmentioning
confidence: 98%
“…Gadolinium‐enhanced MRI helps with the differentiation of scar tissue (postoperative epidural fibrosis) from recurrent or residual disc herniation [128]. Nerve root enhancement (NRE) on postoperative MRI correlates with recurrent or residual symptoms (positive predictive value [PPV] 83.7%) [129]. This correlation was stronger in the presence of both nerve root thickening and recurrent disc herniation [129].…”
Section: Patient Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Contrast enhancement of the nerve root due to inflammation may also occur in patients with persistent or worsened radicular symptoms after lumbar disc surgery, but should not be used for patient selection in the early postoperative phase. 22 Thickening of the nerve root did not occur in successfully operated patients in our study, but is a common nerve root change in patients with persistent pain and can therefore be used as an indicator for unsuccessful lumbar disc surgery. 22 The study strengths are the confirmed acceptable interrater reliability measures of the study parameters, the confirmed clinical treatment success in operated patients, and the use of longitudinal high magnetic field MRI examinations with probably superior imaging quality compared to earlier studies.…”
Section: Discussionmentioning
confidence: 47%
“…22 Thickening of the nerve root did not occur in successfully operated patients in our study, but is a common nerve root change in patients with persistent pain and can therefore be used as an indicator for unsuccessful lumbar disc surgery. 22 The study strengths are the confirmed acceptable interrater reliability measures of the study parameters, the confirmed clinical treatment success in operated patients, and the use of longitudinal high magnetic field MRI examinations with probably superior imaging quality compared to earlier studies. Although 30 patients are sufficient to assess common postoperative image findings, rare postoperative findings may not be encountered or detected.…”
Section: Discussionmentioning
confidence: 47%